Patriotic ayatollahs: nationalism in post-Saddam Iraq - Sayej, Caroleen Marji (Cornell University Press, 2018)
Introduction : the making and unmaking of Iraq -- The ayatollahs and the struggle to maintain legitimacy in the new public sphere -- Sistani, guardian of the democratic process -- Sistani, a guide only -- Quietists turned activists? -- Local and regional sectarian narratives -- Conclusion : rethinking religion and politics : Iraq and beyond